ADDRESSING SOCIAL DILEMMAS WITH MASCOTS, INFORMATION, AND GRAPHICS. (28th March 2019) - Butler, Julianna M.; Fooks, Jacob R.; Messer, Kent D.; Palm‐Forster, Leah H.
Abstract : Reducing nonpoint source pollution is a complex social dilemma involving externalities, information asymmetries, and coordination problems. Using a laboratory experiment, this research investigates how mascots, public information, and data visualization can improve collective group behavior to address a social dilemma. Results show that groups reduce pollution in the experiment when a community mascot expresses negative emotions in response to poor water quality outcomes. Additionally, groups pollute less when they are provided public information about water quality, and abatement is greater when feedback is negatively framed. This study demonstrates how novel nonmonetary incentives can be used to achieve a collective environmental goal. ( JEL D79, Q25, Q52, Q53, D83)